Implementasi Algoritma Least Significant Bit (LSB) untuk Penyembunyian Pesan Teks pada Media Citra Digital dan Audio Berbasis Python - Zulfathan Akbar; Muhammad Nafis; Daniel El Hakim; Muhammad Ichsan Faqih (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Information security is a crucial aspect of modern digital data exchange. Conventional security techniques, such as cryptography, often raise suspicion from third parties due to the production of unreadable encrypted data. Therefore, steganography techniques are required to conceal the very existence of secret messages within other media. This study aims to design and build a Python-based steganography application capable of embedding text messages into PNG digital images and WAV audio formats. The method employed is the Least Significant Bit (LSB), which works by manipulating the rightmost bit of image pixel data or audio samples. The application is built using the Tkinter library for the interface, alongside Pillow and Wave for media processing. Black Box testing results indicate that the application successfully performs message encoding and decoding processes accurately without compromising data integrity. Perceptually, both visually and auditorily, the resulting steganographic media suffer no significant quality degradation, making it effective in deceiving human senses and maintaining information confidentiality.